Preliminary study of canine distemper virus transmission from small mammals to Malayan tiger at Kampung Besul Lama, Terengganu, Malaysia - Lazarus, Bryan Andrew; Mohd Sadali, Muhammad Farris; Kamal, Farina Mustaffa; Hua, Khor Kuan; Abdul Wahab, Ridhwan; Kaderi, Mohd Arifin; Abdullah, Mohd Lutfi; Tengku Azizan, Tengku Rinalfi Putra; Ahmad, Hafandi (Veterinary World, 2025)
Background and Aim: The increasing human-wildlife interface due to urbanization and agricultural expansion has escalated the risk of zoonotic and interspecies disease transmission. Canine distemper virus (CDV), a highly contagious Morbillivirus, has been documented in various carnivorous and non-carnivorous species. In 2019, Malaysia reported its first case of CDV infection in a wild Malayan tiger (Panthera tigris malayensis) named Awang Besul in Kampung Besul Lama, Terengganu. However, the potential role of small mammals as intermediate hosts in CDV transmission remains poorly understood. This study aimed to investigate the role of small mammals as potential reservoir hosts for CDV and to provide molecular confirmation of CDV infection in these species, thereby assessing their role in enzootic viral maintenance and cross-species transmission to apex predators like the Malayan tiger. Materials and Methods: Wildlife sampling was conducted between July 2023 and May 2024 in Kampung Besul Lama, where CDV was previously detected in a Malayan tiger. A total of 77 small mammals from different species were captured using baited live traps. Species identification was performed based on morphological characteristics. Biological samples were collected through nasal and ocular swabs and analyzed using reverse transcription polymerase chain reaction to detect CDV RNA. Positive isolates were subjected to sequencing and Nucleotide Basic Local Alignment Search Tool analysis for molecular characterization. Results: Molecular detection confirmed CDV RNA in three common tree shrews (Tupaia glis), marking the first documented case of CDV in this species. Phylogenetic analysis of the viral hemagglutinin (H) gene revealed a 99.50% nucleotide similarity to a previously reported Malaysian CDV strain (BesulMY/Malaysia/PP894823.1). These findings suggest that small mammals may act as overlooked reservoir hosts, facilitating viral maintenance and spillover between domestic animals and wildlife. Conclusion: This study provides the first molecular evidence of CDV infection in tree shrews, highlighting their potential role in sustaining CDV in an enzootic state and acting as a conduit for interspecies transmission. Given the critically endangered status of Malayan tigers, targeted CDV surveillance and One Health-based disease mitigation strategies are essential to prevent further spillover events that could accelerate species decline.